: ازدياد ظاهرة الطّلاق في محافظة شمال الباطنة بسلطنة عمان أسبابه وآثاره وعلاجه في ضوء مقاصد الشّريعة الإسلاميّة - بلوشي، إبراهيم علي إبراهيم (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2022)
This study aims to highlight the issue of the increase in the divorce phenomenon in the province of North Batinah in Oman, and to clarify the reasons that led to the emergence of this phenomenon in the society. It is also to show the effects on both of divorced spouses and their children and the rest of society, and to reach an appropriate treatment that can contribute to minimizing and reducing the size of divorce in society. The researcher followed four scientific approaches in addressing this subject, through the inductive approach. The researcher extrapolated the sources related to the subject through Omani society in accordance with the rules of Islamic law purposes. In addition, the study analyzed the scientific material through analytical method in order to find out the Islamic opinion in some of the provisions of divorce. As for the comparative approach, a comparison was conducted in digital statistics among the province's states. The field study was also employed by using the questionnaire distributed to the community members, as well as conducting some interviews with divorce specialists. The study found that divorce became apparent in the province of North Batinah in Oman, by increasing its numbers year after year by comparing the numbers of male and female divorcees in the years of study. In addition, there are some reasons that the researcher did not expect to be the main reasons for divorce in society, such as infidelity, as the researcher concluded his study with a set of recommendations.